2020
DOI: 10.1097/cm9.0000000000001138
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs of bone marrow mesenchymal stem cell-derived exosomes regulate acute myeloid leukemia cell proliferation and apoptosis

Abstract: Background: Acute myeloid leukemia (AML) is a malignant hematological disease, originating from hematopoiesis stem cell differentiation obstruction and clonal proliferation. New reagents or biologicals for the treatment of AML are urgently needed, and exosomes have been identified as candidate biomarkers for disease diagnosis and prognosis. This study aimed to investigate the effects of exosomes from bone marrow mesenchymal stem cells (BMSCs) on AML cells as well as the underlying microRNA (miRNA)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…By contrast, EVs derived from healthy MSCs (HD-MSC-EVs) suppress cell proliferation and promote apoptosis in KG-1a cells, likely acting through miR-124-5p [ 49 ]. HD-MSC-EVs transfer miR-222-3p to THP-1 cells and exert pro-apoptotic effects targeting the IRF2/INPP4B signaling pathway [ 50 ]. However, in another study HD-MSC-EVs promote resistance to cytarabine via the upregulation of S100A4, a calcium-binding protein with a prominent role in tumorigenesis [ 51 ].…”
Section: The Stromal-dependent Anti-apoptotic Effectsmentioning
confidence: 99%
“…By contrast, EVs derived from healthy MSCs (HD-MSC-EVs) suppress cell proliferation and promote apoptosis in KG-1a cells, likely acting through miR-124-5p [ 49 ]. HD-MSC-EVs transfer miR-222-3p to THP-1 cells and exert pro-apoptotic effects targeting the IRF2/INPP4B signaling pathway [ 50 ]. However, in another study HD-MSC-EVs promote resistance to cytarabine via the upregulation of S100A4, a calcium-binding protein with a prominent role in tumorigenesis [ 51 ].…”
Section: The Stromal-dependent Anti-apoptotic Effectsmentioning
confidence: 99%
“…BMSCs are used as important seed cells for tissue engineering because of their multipotency, immunomodulatory, and differentiative functions [ 39 ]. BMSCs regulate the bone marrow microenvironment of AML through the paracrine pathway, with exosomes being the main paracrine substances in BMSCs [ 40 ]. Exosomes are considered a novel intercellular signaling modality harboring miRNAs that can be transferred to recipient cells, which in turn regulate the expression of targeted genes in the cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, exosomal miR-139-5p derived from BMSCs inhibited bladder carcinogenesis by targeting PRC1 [ 34 ]. Similarly, exosome-secreted miR-124-5p promoted apoptosis in AML by inhibiting the expression of BMSCs [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MSC-derived exosomes transfected with miRNAs have been shown to play essential roles in tumorigenesis and can serve as mediators in human cancers. Several studies have reported that exosomes released from bone marrow mesenchymal stem cells (MSCs) can carry microRNAs (miRNAs), which are involved in cancer cell proliferation, differentiation, and apoptosis [26][27][28]. However, the effect of human BMSC (hBMSC)-derived exosomes on the occurrence and progression of DLBCL remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%